2006
DOI: 10.1542/peds.2005-2522
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary Dysplasia in Very Low Birth Weight Subjects and Lung Function in Late Adolescence

Abstract: Subjects of very low birth weight with bronchopulmonary dysplasia in the newborn period have poorer lung function in late adolescence than those without bronchopulmonary dysplasia, and their lung function may be deteriorating at a more rapid rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
242
4
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(269 citation statements)
references
References 15 publications
9
242
4
11
Order By: Relevance
“…And like children born prematurely who are often rehospitalized when infected with respiratory syncytial virus, 20,21 adult mice exposed to neonatal hyperoxia show increased susceptibility to influenza A virus infection. 33 Since lung function in late adolescents born prematurely might be deteriorating faster than expected, 24 we decided to investigate whether deficits in lung function and structure changed as oxygen-exposed mice aged. We found elevated lung compliance and reduced tissue elastance activity in aged mice, similar to the changes observed at 8 weeks following exposure to neonatal hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And like children born prematurely who are often rehospitalized when infected with respiratory syncytial virus, 20,21 adult mice exposed to neonatal hyperoxia show increased susceptibility to influenza A virus infection. 33 Since lung function in late adolescents born prematurely might be deteriorating faster than expected, 24 we decided to investigate whether deficits in lung function and structure changed as oxygen-exposed mice aged. We found elevated lung compliance and reduced tissue elastance activity in aged mice, similar to the changes observed at 8 weeks following exposure to neonatal hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Abnormalities in airflow obstruction and air trapping persist into adolescence. [22][23][24][25][26] Similarly, newborn animals exposed to Ն65% oxygen and recovered in room air develop long-term changes in airway responsiveness and increased lung volumes. [27][28][29][30][31] We previously reported that 8-week-old adult mice exposed to Ն60% oxygen for the first 4 days of life have simplified alveoli attributed to changes in elastin expression and an imbalance in alveolar epithelial type I and II cells.…”
mentioning
confidence: 99%
“…4 Development of lung function from childhood to adulthood is debated and not well understood, and longitudinal studies are few. [9][10][11] Normally, after childhood growth, lung function attains a stable plateau before onset of a physiological age-related decline. 12 The maximum level obtained, the duration of the plateau and the rate of the decline predict if and when obstructive pulmonary disease will occur in later life.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, antenatal steroid administrations to mothers in preterm labor, and the application of exogenous surfactant and mild ventilation strategies to premature babies, have markedly reduced their mortality. Unfortunately, survivors continue to show decreased lung capacity at 5-10 years of age and even as young adolescents (2)(3)(4). Moreover, these children are at increased risk for asthma, infection, and other respiratory diseases, and are often rehospitalized after respiratory infection (5,6).…”
mentioning
confidence: 99%